Începuturile teatrului în Egiptul antic - Abou Soughaire, Tarik (Theatrical Research, 2023)
The Beginnings of Theater in Ancient Egypt Performing art has been known in Egypt since the dawn of history, or better, since the time of the pharaohs. It is a reality that no one can deny. But some realities create discord between historians, such as the one we discuss in this article which is expressed in the following question: Did ancient Egypt know the theater? In order to be able to give an exact answer to this question and make the reality indisputable, it was, therefore, necessary to leaf through history trying to bring out the opinions and contradictory opinions, the opinions which are for this reality affirming that the theater was born in Egypt and developed in Greece and those who claim that the theater is a creation of Greek genius. In this article, we will therefore attempt to highlight this discord that existed between historians before discovering the roots of this reality by resorting to specific historical and archaeological clues and to articulate the characteristics of the theater at this time, the interest of the contemporary Egyptian state towards the buildings in which the shows of this period were played, as well as the interest of certain modern Egyptian playwrights for the aspects of pharaonic life of which they are the source of inspiration for some of their works.